A nonhuman primate model for genital herpes simplex virus 2 infection that results in vaginal vesicular lesions, virus shedding, and seroconversion. - Kening Wang; Tristan Jordan; Kennichi Dowdell; Richard Herbert; Ian N Moore; David M Koelle; Jeffrey I Cohen (PLoS Pathogens)
The most commonly used animal models for evaluating the efficacy of HSV-2 candidate vaccines are mice and guinea pigs. While numerous HSV-2 vaccine candidates have been tested in these animals and were effective in reducing disease and mortality, these results did not predict the effectiveness of the vaccines in human trials. Infection of rhesus macaques rarely results in lesions or HSV-2 specific antibody responses. In seeking an animal model that better recapitulates human disease and that might be more predictive of the efficacy of prophylactic vaccines than mice and guinea pigs, we evaluated Cebus apella (C. apella), a New World primate, in an HSV-2 genital infection model. Infectious HSV-2 was cultured from vaginal swabs from all 4 animals for 9-14 days after intravaginal inoculation of HSV-2 seronegative monkeys. Two of 4 monkeys had vesicular lesions in the vagina or vulva. No neurological symptoms were noted. Recurrent lesions and HSV-2 DNA shedding after acute disease resolved was infrequent. UV irradiation of the genital area did not induce recurrent genital lesions or virus shedding. All 4 monkeys developed HSV-2 neutralizing antibodies as well as virus-specific CD4 and CD8 T cell responses. Reinfection of animals 15 to 19 months after primary infection did not result in lesions; animals had reduced virus shedding and a shorter duration of shedding compared with that during primary infection, suggesting that primary infection induced protective immunity. Primary fibroblasts from C. apella monkeys supported the growth of HSV-2 in vitro; in contrast, HSV-2 did not replicate above the titer of the input inoculum in fibroblasts from rhesus macaques. These observations suggest that the C. apella monkey has potential to serve as a model for evaluating the efficacy of prophylactic vaccines, antivirals, or monoclonal antibodies to HSV-2.